(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Background: Hospital acquired urinary tract infection among the hospitalized catheterized patient due to different indications are a common morbility. The objective of study to see the prevalence hospital acquired urinary tract infection among the patients of indwelling catheter admitted in the department Medicine of Chittagong Medical College Hospital. Methods: It was a hospital based obsevational study conducted on purposively selected (Non-probability) hospitalized patients who got indwelling catheter had admitted into the Medicine ward, Chittagong Medical College Hospital from 1st January 2013 to 30th June 2013. Total 50 patients were selected. Urine was analyzed for growth of organism and sensitivity was also done in case where growth was positive. Data was analyzed by statistical method with the software SPSS-20. Results: Results showed that 15 (30%) developed bacteriuria or urinary tract infection with catheter. Development of bacteriuria was not affected by sex, age. People who introduce the catheter has some influence with the occurrence of UTI. E.coli, Klebsella, Proteas and Pseudomonas aeroginosa were the most common bacteria isolated. Imepenam was found the most sensitive antibiotic. Conclusion: Catheter play an important risk for occurrence of UTI. So it should be avoided if possible. Chatt Maa Shi Hosp Med Coll J; Vol.17 (1); Jan 2018; Page 42-45